Quality of life of adolescents with cerebral palsy: agreement between self-report and caregiver's report* - Mariana Ceravolo Ferreira; Nathália Ribeiro Garcia; Cejane Oliveira Martins Prudente; Maysa Ferreira Martins Ribeiro (Universidade de São Paulo, 2020)
Objective: to assess the quality of life (QOL) of adolescents with cerebral palsy (CP) by self-report and by the caregiver's report, and to analyze the agreement between these reports. Method: cross-sectional study conducted with 101 adolescents with CP and 101 caregivers. Both answered the Pediatric Quality of Life Inventory (PedsQL), module 4.0 - Generic (PedsQL 4.0) and module 3.0 - PC (PedsQL 3.0). Agreement between reports was analyzed using the Mann-Whitney test and the intra-class correlation coefficient (ICC) (p<0.05). Results: the lowest scores were in physical health, school activities and fatigue in the self-report. The lowest scores were in physical health and daily activities, in the caregivers' report. Perceptions among adolescents and caregivers differed in physical health, movement and equilibrium, daily and school activities, with a lower score for caregivers in all of them. The agreement between the self-report and the caregivers' report was poor (ICC<0.44) and in both instruments, the caregivers' report was less optimistic. Conclusion: physical health is the most impaired domain of the QOL of adolescents with CP, both in the self-report and in the caregivers' report. However, there is poor agreement between these reports, emphasizing that the use of the caregivers' report should be cautious.